Assessing the physical activity training needs and preferences of community health workers in South Africa - Mark Stoutenberg; Blanca S. Noriega Esquives; Ruth G. St Fleur; Susanna S. Koen; Estelle D. Watson; Francia G. Portacio; Georgia Torres (BMC Public Health)
Abstract Background Emerging work highlights the potential of community health workers (CHWs) to promote physical activity (PA) as a part of their role in preventing and managing non-communicable diseases. However, little is known about CHW preferences and desires towards receiving PA training. Methods Community health promoters (CHPs), a type of CHWs in South Africa, from seven health districts in Johannesburg participated in a day-long in-service training on PA and healthy eating. Prior to the training, CHPs completed a 22-item questionnaire assessing their PA attitudes, beliefs, past promotion efforts, and previous PA training. CHPs were divided into small focus groups to discuss their roles, amount and type of PA training they had received, perceived PA knowledge, and desire for future PA training. A mixed methods approach triangulated data from the questionnaire and the focus groups. Results Seventy-six CHPs attended the in-service training, completed the questionnaire, and participated in one of ten focus groups. CHPs were 38.5 (± 9.2) years of age, 58.7% were male, and 85.3% had > 2 years of experience. Nearly all felt PA was beneficial for health (89.5%) and that promoting it was a part of their job (85.3%). Most CHPs felt that they had sufficient PA knowledge (93.1%) and reported knowing global PA guidelines (90.5%). However, only 10.5% correctly identified the guidelines for aerobic activity or muscle-strengthening, and none correctly identified both. CHPs expressed great interest in receiving additional PA training (98.5%) and applying it in their work (97.1%). Five themes emerged from the focus groups: (1) roles and responsibilities in health promotion and disease prevention; (2) receiving ongoing training to enhance knowledge and skills; (3) increasing their PA training to foster healthier lifestyles in their communities; (4) desired structure of future PA trainings; and (5) strategies for applying the PA training. Conclusions This work provides further evidence for the potential of CHWs to take on a greater role in disease prevention, such as promoting PA. However, future research needs to explore strategies to: provide regular, ongoing PA training, enhance internal team dynamics, and integrate PA promotion as a regular part of their clinical responsibilities and community outreach.